2015
DOI: 10.3323/jcorr.64.497
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tantalum Addition on Crevice Corrosion of Super Duplex Stainless Steels

Abstract: The inclusion control is essential for the development of duplex stainless steels with high local corrosion resistance. In this study, the effect of the inclusion control by Ta addition on the crevice corrosion resistance of the super duplex stainless steels was investigated. The Ta-bearing super duplex stainless steels exhibited the higher crevice corrosion resistance compared to the super duplex stainless steels without Ta. In the super duplex stainless steels without Ta, the dissolution of MnS was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…34,35) As an example of studying the addition of Ta to corrosion-resistant alloys, Takizawa et al showed that the Ta addition enhanced the crevice corrosion resistance of Ni-based alloy. 36) However, there is little or no report on the effect of Ta addition on the formation of inclusions and the pitting corrosion resistance of DSS. For the practical stainless steels, both deoxidization and desulfurization were often conducted by the addition of deoxidizer and desulfurization agents such as Al and Ca.…”
Section: Introductionmentioning
confidence: 99%
“…34,35) As an example of studying the addition of Ta to corrosion-resistant alloys, Takizawa et al showed that the Ta addition enhanced the crevice corrosion resistance of Ni-based alloy. 36) However, there is little or no report on the effect of Ta addition on the formation of inclusions and the pitting corrosion resistance of DSS. For the practical stainless steels, both deoxidization and desulfurization were often conducted by the addition of deoxidizer and desulfurization agents such as Al and Ca.…”
Section: Introductionmentioning
confidence: 99%